In-silico investigation of systematic missense mutations of middle east respiratory coronavirus spike protein - Rhoades, Raina; Sobitan, Adebiyi; Mahase, Vidhyanand; Gebremedhin, Brhan; Tang, Qiyi; Rawat, Danda; Cao, Hongbao; Teng, Shaolei (Frontiers in Molecular Biosciences, 2022)
Middle East Respiratory Syndrome Coronavirus (MERS-CoV) causes severe pneumonia-like symptoms and is still pose a significant threat to global public health. A key component in the virulence of MERS-CoV is the Spike (S) protein, which binds with the host membrane receptor dipeptidyl peptidase 4 (DPP4). The goal of the present investigation is to examine the effects of missense mutations in the MERS-CoV S on protein stability and binding affinity with DPP4 to provide insight that is useful in developing vaccines to prevent coronavirus infection. We utilized a saturation mutagenesis approach to simulate all possible mutations in the MERS-CoV full-length S, S Receptor Binding Domain (RBD) and DPP4. We found the mutations in MERS-CoV S residues, G552, C503, C526, N468, G570, S532, S451, S419, S465, and S435, affect protein stability. We identified key residues, G538, E513, V555, S557, L506, L507, R511, M452, D537, and S454 in S RBD are important in the binding of MERS-CoV S to the DPP4 receptor. We investigated the effects of MERS-CoV S viral variants on protein stability and binding affinity. In addition, we studied all DPP4 mutations and found the functional substitution R336T weakens both DPP4 protein stability and S-DPP4 binding affinity. We compared the S structures of MERS-CoV, SARS-CoV, and SARS-CoV-2 viruses and identified the residues like C526, C383, and N468 located in equivalent positions of these viruses have effects on S structure. These findings provide further information on how mutations in coronavirus S proteins effect protein function.